2016
DOI: 10.1109/tuffc.2016.2535440
|View full text |Cite
|
Sign up to set email alerts
|

On the Feasibility of Quantifying Fibrous Cap Thickness With Acoustic Radiation Force Impulse (ARFI) Ultrasound

Abstract: Acute cerebrovascular accidents are associated with the rupture of vulnerable atherosclerotic plaques in the carotid arteries. Fibrous cap thickness has been shown to be an important predictor of plaque rupture, but has been challenging to measure accurately with clinical noninvasive imaging modalities. The goals of this investigation were first, to evaluate the feasibility of using transcutaneous acoustic radiation force impulse (ARFI) ultrasound to quantify fibrous cap thickness and second, to optimize both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…higher than 0.5 mm) with a relatively significant predictive value. Finally, the overestimation bias across all three readers matched nearly identically to the mean positive bias predicted by finite element (FE) simulation in previous work (0.13 ± 0.05 mm) for the equivalent imaging parameters 24 . Given the considerably larger standard deviation on the reader’s measurements as compared to FE (±0.3 mm vs. ±0.05 mm), further investigation is needed to demonstrate the limits of ARFI FC thickness measurement, but nevertheless, the level of agreement between FE prediction and in vivo measurements was highly encouraging.…”
Section: Discussionsupporting
confidence: 81%
“…higher than 0.5 mm) with a relatively significant predictive value. Finally, the overestimation bias across all three readers matched nearly identically to the mean positive bias predicted by finite element (FE) simulation in previous work (0.13 ± 0.05 mm) for the equivalent imaging parameters 24 . Given the considerably larger standard deviation on the reader’s measurements as compared to FE (±0.3 mm vs. ±0.05 mm), further investigation is needed to demonstrate the limits of ARFI FC thickness measurement, but nevertheless, the level of agreement between FE prediction and in vivo measurements was highly encouraging.…”
Section: Discussionsupporting
confidence: 81%
“…There are currently research studies to utilize elastography and ARFI in characterizing plaques quantitatively in terms of elasticity modulus or shearwave speed (radially along the vessel cross section circumference as well as longitudinally along vessel length) or qualitatively based on the characteristic of plaques such as stiff/soft/stiff layers corresponding to vessel wall/lipid/calcified lesion respectively (Ramnarine 2014, Russell 2009). Recent in-vivo studies have shown compelling results of ARFI in characterizing fibrous cap thickness and mechanical properties of different layers in human carotid plaques (Czernuszewicz 2015, Czernuszewicz 2016). With diffused disease like fatty liver, there is a possibility for elastography to identify fatty liver using shearwave dispersion which can be quantified in terms of viscosity parameter.…”
Section: Discussionmentioning
confidence: 99%